Dampak Bea Keluar Kakao Indonesia terhadap Country Market Power di Pasar Biji Kakao Amerika Serikat dan Terms of Trade - Ari Harsanti; Bambang Juanda; Sahara Sahara (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2014)
As the world’s third-largest cocoa beans producer, Indonesia is expected to have a comparative advantage and to become cocoa beans price reference. This research investigates market power of Indonesia cocoa beans export for the United State market as an impact of an export tax. Five cocoa beans exporting countries namely Cote d’Ivoire, Ecuador, Ghana, Dominica Rep and Nigeria are calculated their market power as Indonesia’s competitors by estimating residual demand elasticity with two stage least square method. The results show that Indonesia’s market power suffered after imposing the export tax. Cote d’Ivoire and Ghana get advantages from this export restriction. The effect of export tax on welfare is analyzed by calculating terms of trade. The gain from cocoa beans trade depicts a declining terms of trade for dealing with the international cocoa beans market.